Sialic acids Neu5Ac and KDN in adipose tissue samples from individuals following habitual vegetarian or non-vegetarian dietary patterns - Guerrero Flores, Gerardo Nataniel (2023)
Sialic acids (Sias) are a class of sugar molecules with a parent nine‑carbon neuraminic acid, generally present at the ends of carbohydrate chains, either attached to cellular surfaces or as secreted glycoconjugates. Given their position and structural diversity, Sias modulate a wide variety of biological processes. However, little is known about the role of Sias in human adipose tissue, or their implications for health and disease, particularly among individuals following different dietary patterns. The goal of this study was to measure N‑Acetylneuraminic acid (Neu5Ac), N‑Glycolylneuraminic acid (Neu5Gc), and 2‑keto‑3‑deoxy‑d‑glycero‑d‑galacto‑nononic acid (KDN) concentrations in adipose tissue samples from participants in the Adventist Health Study‑2 (AHS‑2) and to compare the abundance of these Sias in individuals following habitual, long‑term vegetarian or non‑vegetarian dietary patterns. A method was successfully developed for the extraction anddetection of Sias in adipose tissue. Sias levels were quantified in 52 vegans, 56 lacto‑vegetarians, and 48 non‑vegetarians using LC–MS/MS with Neu5Ac‑D‑1,2,3‑13 C 3 as an internal standard. Dietary groups were compared using linear regression. Vegans and lacto‑ovo‑vegetarians had significantly higher concentrations of Neu5Ac relative to non‑vegetarians. While KDN levels tended to be higher in vegans and lacto‑ovo‑vegetarians, these differences were not statistically significant. However, KDN levels were significantly inversely associated with body mass index. In contrast, Neu5Gc was not detectedin human adipose samples. It is plausible that different Neu5Ac concentrations in adipose tissues of vegetarians, compared to those of non‑vegetarians, reflect a difference in the baseline inflammatory status between the two groups. Epidemiologic studies examining levels of Sias in human adipose tissue and other biospecimens will help to further explore their roles in development and progression of inflammatory conditions and chronic diseases.